Coupling image denoising model based on total variation - Mei-ling WANG; Xian-chun ZHOU; Lin-feng ZHOU; Lan-fang SHI (Tongxin xuebao)
The total variation (TV) model used in image denoising may produce “staircase effect”. A coupling image de-noising model based on total variation was proposed. First, a trend fidelity term based on the change tendency of image gradient was established. The fidelity term could not only remove image noise, but also restrain “staircase effect”. Then, wavelet was used to decompose coefficient in frequency domain, control based on the edge detection ability of Canny algorithm were designed. The control functions control energy spread direction, the advantages of TV model and trend fidelity term are maintained, edge and texture details were protected, and “staircase effect'' was also suppressed. Experiment results show that peak signal to noise ratio (PSNR), structure similarity (SSIM) and visual effects of the nov-el model are much better. Moreover, the running time of the novel model is shorter.